Characteristics of stroke after liver and kidney transplantation - Kwon, Hanim; Shin, Sung; Baek, Chung Hee; Chang, Jun Young; Kang, Dong-Wha; Kwon, Sun U.; Kim, Jong S.; Kim, Bum Joon (Frontiers in Neurology, 2023)
Background The mechanism and characteristics of a post-transplantation stroke may differ between liver (LT) and kidney transplantation (KT), as the associated comorbidities and peri-surgical conditions are different. Herein, we investigated the characteristics and etiologies of stroke occurring after LT and KT. Methods Consecutive patients who received LT or KT between January 2005 to December 2020 who were diagnosed with ischemic or hemorrhagic stroke after transplantation were enrolled. Ischemic strokes were further classified according to the etiologies. The characteristics of stroke, including in-hospital stroke, perioperative stroke, stroke etiology, and timing of stroke, were compared between the LT and KT groups. Results There were 105 (1.8%) and 58 (1.3%) post-transplantation stroke patients in 5,950 LT and 4,475 KT recipients, respectively. Diabetes, hypertension, and coronary arterial disease were less frequent in the LT than the KT group. In-hospital and perioperative strokes were more common in LT than in the KT group (LT, 57.9%; KT, 39.7%; p = 0.03, and LT, 43.9%; KT, 27.6%; p = 0.04, respectively). Hemorrhagic strokes were also more common in the LT group (LT, 25.2%; KT, 8.6%; p = 0.01). Analysis of ischemic stroke etiology did not reveal significant difference between the two groups; undetermined etiology was the most common, followed by small vessel occlusion and cardioembolism. The 3-month mortality was similar between the two groups (both LT and KT, 10.3%) and was independently associated with in-hospital stroke and elevated C-reactive protein. Conclusions In-hospital, perioperative, and hemorrhagic strokes were more common in the LT group than in the KT group. Ischemic stroke subtypes did not differ significantly between the two groups and undetermined etiology was the most common cause of ischemic stroke in both groups. High mortality after stroke was noted in transplantation patients and was associated with in-hospital stroke.